Citra Perempuan Madura dalam Novel Damar Kambang Karya Muna Masyari - Wahyudin, Sapta Arif Nur (Jurnal Bahasa dan Sastra, 2024)
This study aims to describe the image of Madurese women in the novel Damar Kambang by Muna Masyari. This research uses a qualitative descriptive method. The source of research data is the novel Damar Kambang by Muna Masyari. Data were collected by note-taking technique. That is, the researcher reads the work carefully, then records the data containing images of women. In analyzing the data, the researcher uses the theory of Miles and Huberman, namely (1) identifying the novel Damar Kambang by Muna Masyari, (2) reducing the data, (3) presenting the data, (4) interpreting the data, (5) concluding the results of the interpretation . There are three social images of women found in the novel Damar Kambang by Muna Masyari, namely (1) the traditional role of women as children in the family; (2) The traditional role of women as wives; and (3) Women as objects of psychological and physical violence. Apart from that, Muna Masyari also succeeded in introducing a culture of courtesy, reverence for parents and teachers, a family attitude, to a hard side both physically and psychologically for women. This novel can be a social reflection of readers in society.